Case reportA 6-year-old boy with Sulzberger and Garbe dermatosis: a case report and literature review - Tabara, Katarzyna; Noweta, Marcin; Bienias, Wojciech; Kaszuba-Bartkowiak, Katarzyna; Kaszuba, Andrzej (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Sulzberger-Garbe disease was described in 1937. Not more than a hundred of cases of the disease have been reported in the literature. Despite a quite specific picture, there are no features that could undeniably be attributed to this particular disease entity. Discoid exudative and lichenoid lesions are main lesions in this dermatosis. The disease is associated with severe pruritus. The lesions are located on the trunk and extremities as well as the genitals. Eosinophilia is frequently found in the course of the disease. Sulzberger-Garbe dermatosis has been diagnosed mainly in middle-aged males of Jewish origin but it can occur in both sexes at any age. Good therapeutic response to systemic corticosteroids has been observed. It is still controversial whether the disease should be classified as an independent clinical entity.